2001
DOI: 10.1097/00003246-200104000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Blunted erythropoietic response to anemia in multiply traumatized patients

Abstract: Multiply traumatized patients exhibit an inadequate EPO response to low hemoglobin concentrations. Thus, anemia in severe trauma is the result of a complex network of bleeding, blunted EPO response to low hemoglobin concentrations, inflammatory mediators, and a hypoferremic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…A survival time-dependent elevation in serum EPO level was detected for blunt injuries and fire fatality, suggesting the systemic influence of anemia/hypoxia following massive bleeding and/or tissue damage [33][34][35]. Similar findings for gastrointestinal bleeding and infectious diseases may be related to the severity and duration of bleeding/anemia or advanced hypoxia in the death process [35][36][37][38].…”
Section: Discussionmentioning
confidence: 62%
“…A survival time-dependent elevation in serum EPO level was detected for blunt injuries and fire fatality, suggesting the systemic influence of anemia/hypoxia following massive bleeding and/or tissue damage [33][34][35]. Similar findings for gastrointestinal bleeding and infectious diseases may be related to the severity and duration of bleeding/anemia or advanced hypoxia in the death process [35][36][37][38].…”
Section: Discussionmentioning
confidence: 62%
“…1,[3][4][5][6][7] Recently, Krafte-Jacobs and colleagues demonstrated this phenomenon in critically ill children. 5 They showed that patients who were acutely anemic had serum erythropoietin concentrations that were significantly lower than erythropoietin concentrations measured in chronically anemic patients.…”
Section: Discussionmentioning
confidence: 95%
“…3 Adult patients who received rHuEPO 300 units/kg/day for 5 days, then every other day, were transfused with significantly fewer units of RBCs when compared with patients who did not receive rHuEPO. Currently, data demonstrating that rHuEPO reduces the number of RBC transfusions pediatric intensive care unit (PICU) patients receive is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…7,12,13 However, their bone marrow may respond to exogenous erythropoietin (EPO) and this possibility has been explored in two clinical trials, including almost 1,500 intensive care unit (ICU) patients, conducted by Corwin et al 14,15 Compared to placebo, those patients treated with EPO received less ABT and achieved a higher hematocrit. However, there were no significant differences regarding morbid-mortality.…”
Section: Postoperative Anemia and Erythropoietinmentioning
confidence: 99%